Development of Internet of Things (IoT) Based Electric Equipment Control - Fathahillah Fathahillah; Satria Gunawan Zain; Wirawan Setialaksana; Muh. Asriadi (International Journal of Environment, Engineering and Education, 2022)
The Internet of Things (IoT) is one of the new trends in the world of technology that is likely to be one of the big things in the future. IoT is a concept that aims to expand the benefits of continuously connected internet connectivity. IoT can combine physical and virtual objects by exploiting data capture and communication capabilities. This development research aims to produce an IoT-based electrical equipment control system. The development model used in this research is the prototype development model. The development procedure consists of 6 steps: Requirements Analysis, Building Prototypes, Evaluation of Prototypes, Coding the System, Testing and Evaluating the System, and Implementing the System. The equipment used for the IoT-based electronic control system that will be designed consists of raspberry pi, power supply, relays, speakers, sound sensors, and lights. The results of this study resulted in an electronic control system that was carried out by voice commands. In this study, IoT devices were programmed to respond to commands to turn on/off the porch light, turn on/off the living room light, turn on/off the kitchen light, and turn on/off the bedroom light. The results of testing and evaluation of the system indicate that the development of this control system can work well, and the device works according to the instructions. The minimum distance for the voice command response to the device is 0 -10 cm, and the maximum length for the voice command response to the device is 500 cm.